Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.9790/3013-0401201028041
|View full text |Cite
|
Sign up to set email alerts
|

A review on chemistry and biological significance of benzimidaole nucleus

Abstract: Benzimidazole is a heterocyclic aromatic organic compound. It is an important pharmacophore and privileged structure in medicinal chemistry. It plays a very important role with plenty of useful therapeutic activities such as : antiulcers, antihypertensives, analgesic, anti-inflammatory, anti-virals, antifungals, anticancers, and antihistaminics. The review of the literature shows that the benzimidazole derivatives are outstandingly effective compound and number of reviews available for biochemical and pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Benzimidazole and its derivatives are some of the oldest and chemically most-studied nitrogen-containing aromatic heterocyclic compounds (Srestha et al, 2014). They have a wide range of applications in medicinal chemistry and in biological processes including as anticancer, antiulcer, antifungal and anti-inflammatory agents, and exhibit antimycobacterial and antioxidant activities (El Rashedy & Aboul-Enein, 2013;Gaba et al, 2014;Kathiravan et al, 2012).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Benzimidazole and its derivatives are some of the oldest and chemically most-studied nitrogen-containing aromatic heterocyclic compounds (Srestha et al, 2014). They have a wide range of applications in medicinal chemistry and in biological processes including as anticancer, antiulcer, antifungal and anti-inflammatory agents, and exhibit antimycobacterial and antioxidant activities (El Rashedy & Aboul-Enein, 2013;Gaba et al, 2014;Kathiravan et al, 2012).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The extraordinary properties of benzotriazole moiety have also been harnessed in development of some very promising and efficient ligands particularly for coupling reactions . Recently, 2‐substituted azoles emerged as one of the most fascinating entity which can be understood in terms of remarkable range of biological, pharmaceutical, industrial and analytical significance of benzoxazoles, benzimidazoles, and benzothiazoles . The importance of benzoxazoles can be further visualized in terms of its presence as structural core in diverse range of natural and synthetic molecules, for example, antimycobacterial agents, pseudopteroxazole ( I ), UK‐1 ( II ) AJI9561 ( III ), HIV reverse transcriptase inhibitor L‐697,661 ( IV ), estrogen receptor‐ β agonist ERB‐041 ( V ), selective peroxisome proliferator‐activated receptor γ antagonist JTP‐426467 ( VI ) and anticancer agent NSC‐693638 ( VII ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature showed benzimidazole derivatives to be useful pharmacological compounds in terms of various biochemical and pharmacological studies. [4]…”
Section: Introductionmentioning
confidence: 99%